The resident's satisfaction on gated and guarded homes: case study in Selangor / Muhammad Mujahid Fahmi Mohd Taufiq - Mohd Taufiq, Muhammad Mujahid Fahmi (2023)
This research aimed to measure the level satisfaction on the gated and guarded homes at Taman Puncak Jalil, Seri Kembangan as the case study. The study adopted both exploratory and descriptive research designs, which involved a secondary data research and questionnaire survey to residents of gated and guarded community in Taman Puncak Jalil, Seri Kembangan. Quantitative data collected was analysed using descriptive analysis to identify the elements of gated and guarded community and investigate the resident's level of satisfaction on elements of gated and guarded community. Findings from this research shows the Taman Puncak Jalil is not the only residential area which operates as a gated and guarded community. As this research found that effective boom gates have the highest satisfaction from residents of gated and guarded community in Taman Puncak Jalil, it shows that the boom gates have proven its effectiveness due to the satisfaction from the residents. It followed by allocation of CCTV in the second, secure perimeter fencing at third, and proper guard house at fourth rank.